Nucleation Theory and Growth of Nanostructures - Dubrovskii, Vladimir G. (NanoScience and Technology, 2014)
Semiconductor nanostructures such as nanowires are promising building blocks of future nanoelectronic, nanophotonic and nanosensing devices. Their physical properties are primarily determined by the epitaxy process which is rather different from the conventional thin film growth. This book shows how the advanced nucleation theory can be used in modeling of growth properties, morphology and crystal phase of such nanostructures. The book represents a systematic account of modern nucleation theory in open systems,  nanostructure nucleation and growth mechanisms, and possibilities for tuning the nanostructure properties to the desired values.